2022
DOI: 10.3389/fpsyt.2022.829918
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Stress Among Poles and How They Cope With Stress During the COVID-19 Pandemic

Abstract: This study aimed to learn about causes of stress among adult Poles and their ways of dealing with stress during the COVID-19 pandemic. A survey questionnaire was used, as well as two standardized research tools: Endler and Parker’s Coping Inventory for Stressful Situations (CISS), and Watson and Clark’s Positive and Negative Affect Schedule (PANAS). The research group comprised 595 people, including 80.5% women. They were 18–75 years old. The most important stress factors were concern for one’s health, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In our study, most of the patients presented differential‐ and mix‐oriented stress coping style; among those who displayed one dominant style, task‐oriented and avoidance‐oriented stress coping style prevailed, while emotion oriented stress coping style was the rarest. This distribution of stress coping style partially overlaps with the distribution shown in other studies: for example, research conducted in Poland during the Covid‐19 pandemic indicated that healthy Poles most often displayed an avoidance‐oriented coping style 23 …”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In our study, most of the patients presented differential‐ and mix‐oriented stress coping style; among those who displayed one dominant style, task‐oriented and avoidance‐oriented stress coping style prevailed, while emotion oriented stress coping style was the rarest. This distribution of stress coping style partially overlaps with the distribution shown in other studies: for example, research conducted in Poland during the Covid‐19 pandemic indicated that healthy Poles most often displayed an avoidance‐oriented coping style 23 …”
Section: Discussionsupporting
confidence: 70%
“…This distribution of stress coping style partially overlaps with the distribution shown in other studies: for example, research conducted in Poland during the Covid-19 pandemic indicated that healthy Poles most often displayed an avoidance-oriented coping style. 23 In our study, the emotion-oriented stress coping style group had the highest stress levels during the hospitalization period. This observation is not consistent with the study by Baliousis et al, 17 where emotion-oriented coping patients undergoing HSCT had lower distress levels than task-and avoidance-oriented coping patients.…”
Section: Discussionmentioning
confidence: 48%
“…Our research conducted at the turn of 2021/2022 showed that the list of concerns experienced by Poles remained unchanged compared to the situation a year earlier. However, these concerns occur more frequently [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Ext, Ser, and Mod predicted higher total stress responses, emotional responses, physical responses, and behavioral responses than NA. Age was only a predictor of emotional response, the middle-aged group ( 36 50 ) was less likely to report higher emotional responses when compared with the younger group ( 18 35 ).…”
Section: Resultsmentioning
confidence: 87%